Pemberdayaan Masyarakat melalui Program BUSADAKO (Buang Sampah Dapat Sembako) di Dusun Sekantong - Fauzi, Akhmad; Wibawanto, Rakhmat H.; Agustyarini, Yhasinta; Maulida, Alvi Fatma; Al-Latif, Ibnu Raihan (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The issue of household waste remains a serious environmental problem in rural areas, including in Sekantong Hamlet, Kunjorowesi Village, Ngoro District, Mojokerto Regency. Low public awareness of waste management and the lack of an organized management system necessitate the need for a community empowerment-based service program. This community service activity aims to enhance environmental awareness while strengthening the socio-economic aspects of the community through the Program BUSADAKO (Buang Sampah Dapat Sembako). The method used is Asset-Based Community Development (ABCD) with the stages of appreciative inquiry, asset mapping, area exploration, financial circulation analysis, and priority scale determination. The community service results indicate a change in public behavior regarding waste disposal and sorting, an increase in citizen participation, and the establishment of an incentive-based waste management system managed by the Karang Taruna. The BUSADAKO program not only impacts environmental cleanliness but also strengthens social solidarity and opens up opportunities for program sustainability at the hamlet level.